2000
DOI: 10.1046/j.1365-2036.2000.00835.x
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole and CYP2C19 polymorphism: effects of long‐term treatment on gastrin, pepsinogen I, and chromogranin A in patients with acid related disorders

Abstract: INTRODUCTIONOmeprazole is a potent inhibitor of gastric acid secretion, widely used in the treatment of gastrooesophageal re¯ux disease (GERD) and peptic ulcer disease. 1, 2 Long-term continuous treatment of GERD SUMMARYBackground: The polymorphic enzyme CYP2C19 is of importance for the metabolism and effects of omeprazole during short-term treatment. Aim: To investigate the relationship between CYP2C19 genotype and the effects of long-term omeprazole treatment. Material and methods: A total of 180 patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 43 publications
3
26
0
Order By: Relevance
“…The usual dosages of OM, alone or combined with other agents, range from 10 to 40 mg/day for adults. Approximately 80% of doses of OM seem to be cleared by cytochrome P450 2C19 (CYP2C19), but altered CYP2C19 activity does not seem to increase the risk of adverse effects (16,20). The rates of common adverse events during treatment with OM in general practice have been reported in several publications.…”
Section: Discussionmentioning
confidence: 99%
“…The usual dosages of OM, alone or combined with other agents, range from 10 to 40 mg/day for adults. Approximately 80% of doses of OM seem to be cleared by cytochrome P450 2C19 (CYP2C19), but altered CYP2C19 activity does not seem to increase the risk of adverse effects (16,20). The rates of common adverse events during treatment with OM in general practice have been reported in several publications.…”
Section: Discussionmentioning
confidence: 99%
“…Bertilsson and collaborators have found that changes in gut pH after treatment by e.g. omeprazole are more pronounced in CYP2C19 PMs (Sagar et al 2000). Long-term treatment of proton pump inhibitors leads to a more extensive gastrin release in PMs as compared to EMs (Sagar et al 2000).…”
Section: Cytochromes P450mentioning
confidence: 99%
“…We found in 72 patients treated for more than one year with 20 mg omeprazole per day, that heterozygous extensive metabolizers had 3 times higher serum gastrin than extensive metabolizers with two functional CYP2C19 alleles (PΩ 0.0001) (Sagar et al 2000). Also concentrations of pepsinogen I and chromogranin A were significantly different in the two genotypic groups.…”
mentioning
confidence: 69%